Selection of Power Semiconductor Switches in Modified Half Bridge Resonant Inverter Fitted Induction Heater in Power Line for Less Harmonic Injection - Pradip Kumar Sadhu; Palash Pal; Nitai Pal; Sourish Sanyal (Institute of Advanced Engineering and Science, 2015)
This paper presents an approach to minimize the harmonics contained in the input current of single phase Modified Half Bridge Resonant inverter fitted induction heating equipment. A switch like IGBT, GTO, and MOSFET are used for this purpose. It analyzes the harmonics or noise content in the sinusoidal input current of this inverter. Fourier Transform has been used to distinguish between the fundamental and the harmonics, as it is a better investigative tool for an unknown signal in the frequency domain. An exhaustive method for the selection of different power semiconductor switches for Modified Half Bridge Resonant inverter fed induction heater is presented. Heating coil of the induction heater is made of litz wire which reduces the skin effect and proximity effect at high operating frequency. With the calculated optimum values of input current of the system at a particular operating frequency, Modified Half Bridge Resonant inverter topology has been simulated using P-SIM software. To obtain the Input current waveforms through it, further analysis has been employed. From this analysis selection of suitable power semiconductor switches like IGBT, GTO and MOSFET are made. Waveforms have been shown to justify the feasibility for real implementation of single phase Modified Half Bridge Resonant inverter fed induction heater in industrial application.